FUNCTIONAL STYLES OF THE ENGLISH LANGUAGE: OVERVIEW AND IMPORTANCE (Лучшие интеллектуальные исследования, 2025)
Colloquial style appears in everyday spoken language and informal writing. It is spontaneous, expressive, and personal.